1991
DOI: 10.1042/bj2790197
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of amylase and chymotrypsinogen expression by dexamethasone and caerulein in serum-free-cultured pancreatic acinar AR4-2J cells. Influence of glucose

Abstract: The direct effects of dexamethasone and caerulein on two pancreatic enzymes, amylase and chymotrypsin, were determined in AR4-2J cells cultured under serum-free conditions at two glucose concentrations (1.0 and 4.5 g/l). In the absence of any hormone, the higher glucose concentration resulted in a 1.6-1.8-fold increase in the basal levels of amylase and chymotrypsinogen. Dexamethasone (50 nM) increased the biosynthesis and mRNA levels of both enzymes at both glucose concentrations. However, dexamethasone had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…On the other hand, SP expression was significantly increased at a lower concentration of 10 Ϫ8 M. The up-regulation of SP was substantially stronger than the upregulation of its gene, PPT-A (3-to 1.5-fold compared with control). It is possible that RNA stabilization, increased translational activity, or reduced degradation of SP by neutral endopeptidases contributed to the observation, although these hypotheses remain to be elucidated (Estival et al, 1991;O'Connor et al, 2004). The 3-fold increase in SP levels is in line with previous experiments done in vivo, in which SP is increased with a similar magnitude in the pancreas after induction of AP (Lau and Bhatia, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, SP expression was significantly increased at a lower concentration of 10 Ϫ8 M. The up-regulation of SP was substantially stronger than the upregulation of its gene, PPT-A (3-to 1.5-fold compared with control). It is possible that RNA stabilization, increased translational activity, or reduced degradation of SP by neutral endopeptidases contributed to the observation, although these hypotheses remain to be elucidated (Estival et al, 1991;O'Connor et al, 2004). The 3-fold increase in SP levels is in line with previous experiments done in vivo, in which SP is increased with a similar magnitude in the pancreas after induction of AP (Lau and Bhatia, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…These results indicated that dexamethasone inhibits growth and induces differentiation of AR42J cell toward an amylase-secreting exocrine phenotype. Our observation was similar to those of previously reported by others for dexamethasone-induced parameters of differentiation (Logsdon et al, 1985;Estival et al, 1991;Rajasekaran et al, 1993). We examined the effect of MAP kinase pathway on amylase mRNA expression induced by dexamethasone.…”
Section: R Esults and Discussionsupporting
confidence: 82%
“…It has been demonstrated that dexamethasone converts them into matured exocrine cells expressing digestive enzymes (Logsdon et al, 1985;Rajasekaran et al, 1993), whereas activin A converts them into insulin-producing neuroendocrine cells (Ohnishi et al, 1995). The dexamethasone-induced phenotypic changes of AR42J cells include increases in secretory organelles (Rajasekaran et al, 1993), tissue specific gene expression (Estival et al, 1991) and receptors for cholecystokinin (Rosewicz et al, 1994). Moreover, glucocorticoids inhibit the growth of animal cells including AR42J cells (Guthrie et al, 1991), another hallmark of cellular differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme secretion in serum-free culture media is linear for 48 h in both unstimulated and stimulated cells [20]. No chymotrypsin activity was detected in either the cells or the secretion before the addition of activating trypsin.…”
Section: Enzyme Inductionmentioning
confidence: 93%